Identification of restorer lines for diversified CMS lines in Sunflower (Helianthus annuus L.): Identification of restorer lines for diversified CMS lines in Sunflower (Helianthus annuus L.) - VIKAS KULKARNI,; M R UMESH,; N G VIJAYKUMAR,; POORNIMA,; H P MEENA, (Journal of Oilseeds Research, 2023)
The material for the study consisted of three stable CMS lines viz., CMS 103A, CMS104A, and CMS 38A as female lines and 50 new inbred lines as testers. All the three CMS lines and 50 inbred lines were crossed in a Line × Tester fashion and resultant 150 hybrids were evaluated for fertility restoration. Among common restorers across all three CMS lines, RCR-20-8 recorded highest gca for seed yield, oil content and plant height, followed by RCR20-19 for head diameter and seed yield; RCR-20-13 for volume weight and early flowering. These lines can be used as testers for developing hybrids and also for development of new tester lines with combination of desirable characters.